Adding Celecoxib With or Without Zoledronic Acid for Hormone-Naïve Prostate Cancer: Long-Term Survival Results From an Adaptive, Multiarm, Multistage, Platform, Randomized Controlled Trial - Mason, Malcolm D; Clarke, Noel W; James, Nicholas D; Dearnaley, David P; Spears, Melissa R; Ritchie, Alastair W S; Attard, Gerhardt; Cross, William; Jones, Rob J; Parker, Christopher C; Russell, J Martin; Thalmann, George N; et al. (Journal of clinical oncology, 2017)
Purpose Systemic Therapy for Advanced or Metastatic Prostate Cancer: Evaluation of Drug Efficacy is a randomized controlled trial using a multiarm, multistage, platform design. It recruits men with high-risk, locally advanced or metastatic prostate cancer who were initiating long-term hormone therapy. We report survival data for two celecoxib (Cel)-containing comparisons, which stopped accrual early at interim analysis on the basis of failure-free survival. Patients and Methods Standard of care (SOC) was hormone therapy continuously (metastatic) or for ≥ 2 years (nonmetastatic); prostate (± pelvic node) radiotherapy was encouraged for men without metastases. Cel 400 mg was administered twice a day for 1 year. Zoledronic acid (ZA) 4 mg was administered for six 3-weekly cycles, then 4-weekly for 2 years. Stratified random assignment allocated patients 2:1:1 to SOC (control), SOC + Cel, or SOC + ZA + Cel. The primary outcome measure was all-cause mortality. Results were analyzed with Cox proportional hazards and flexible parametric models adjusted for stratification factors. Results A total of 1,245 men were randomly assigned (Oct 2005 to April 2011). Groups were balanced: median age, 65 years; 61% metastatic, 14% N+/X M0, 25% N0M0; 94% newly diagnosed; median prostate-specific antigen, 66 ng/mL. Median follow-up was 69 months. Grade 3 to 5 adverse events were seen in 36% SOC-only, 33% SOC + Cel, and 32% SOC + ZA + Cel patients. There were 303 control arm deaths (83% prostate cancer), and median survival was 66 months. Compared with SOC, the adjusted hazard ratio was 0.98 (95% CI, 0.80 to 1.20; P = .847; median survival, 70 months) for SOC + Cel and 0.86 (95% CI, 0.70 to 1.05; P =.130; median survival, 76 months) for SOC + ZA + Cel. Preplanned subgroup analyses in men with metastatic disease showed a hazard ratio of 0.78 (95% CI, 0.62 to 0.98; P = .033) for SOC + ZA + Cel. Conclusion These data show no overall evidence of improved survival with Cel. Preplanned subgroup analyses provide hypotheses for future studies.